Economic determinants of foreign direct investment in Algeria during the period (1990-2024) - Bouchareb, Djalal; guembour, Mohamed Amine; Zemouri, Kamel; Boudjenana, Fouad; Herizh, Hicham (Journal of Ecohumanism, 2026)
This research paper aimed to study the impact of some economic determinants on foreign direct investment inflows to Algeria using the Autoregressive Distributed Lag Periods (ARDL) method during the period from 1990-2024 and relying on the Eviews program. The study concluded that there is a long-term equilibrium relationship between the study variables, which included the exchange rate, GDP, inflation, and imports. Based on the results of the study, which proved that there is a significant positive impact of imports on foreign direct investment inflows, while the inflation, exchange rate, and GDP rate variables had a significant negative impact on foreign direct investment in Algeria.